Sustainability – bringing about a value changes amongst employees - Zangl, Sabine; Husetic, Mirza; Lackner, Maximilian; Lembacher, Harald (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In the past decades, the topic "sustainability" has received increasing attention, and many companies feel obligated to act more sustainably. However, they often face difficulties when trying to implement sustainability-oriented business practices. In order to enable a successful change, the existing convictions and fundamental assumptions of an organizations’ members regarding sustainable thinking and behaviour must be changed. Though some employees do not need to be convinced, a full culture and value change in the organization is necessary for a transformation. The results of this work show that intensive, transparent communication and involvement of the organisation are the keys to success. Through them the employees are made aware and motivated appropriately for contributing towards the topic. Communication is also the tool that enables employees to act out of their own beliefs with a sustainable orientation. The long-term goal is a sustainable anchoring of the new values in the employees’ minds, which is then the basis for corporate action and success.